2012
DOI: 10.1111/aas.12050
|View full text |Cite
|
Sign up to set email alerts
|

Extracorporeal membrane oxygenation in adult patients with severe acute respiratory failure

Abstract: Patients with severe ARDS have a favourable outcome when treated with ECMO and when an ECMO retrieval team establishes the ECMO treatment at the referring hospital. SAPS-II, SOFA and Murray scores predicted the outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2013
2013
2017
2017

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(44 citation statements)
references
References 36 publications
3
41
0
Order By: Relevance
“…There were also no major adverse events during transfer. We have also shown a high survival rate in patients who received ECMO -this exceeds those seen in an earlier randomised prospective trial and the CESAR trial [8,23], and is similar to that seen in more recent studies [18][19][20]. The use of newer veno-venous circuits, oxygenators and centrifugal pumps, and the improved biocompatibility and systemic anticoagulation requirements of heparin-bonded circuits, may go some way to explain these differences [24,25].…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…There were also no major adverse events during transfer. We have also shown a high survival rate in patients who received ECMO -this exceeds those seen in an earlier randomised prospective trial and the CESAR trial [8,23], and is similar to that seen in more recent studies [18][19][20]. The use of newer veno-venous circuits, oxygenators and centrifugal pumps, and the improved biocompatibility and systemic anticoagulation requirements of heparin-bonded circuits, may go some way to explain these differences [24,25].…”
Section: Discussionsupporting
confidence: 82%
“…Despite the lack of surgical involvement common to other studies [18][19][20], there were no cannulation failures or significant ECMO complications. There were also no major adverse events during transfer.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…These findings were echoed in the Conventional Ventilation or ECMO for Severe Adults Respiratory Failure (CESAR) trial, which showed a 63% 6-month survival and a survival without disability benefit for ECMO (p ¼ 0.03) when compared with conventional therapy [5]. Similarly, among 124 patients treated in a 14-year span from 1997 to 2011 in Denmark, Lindskov and colleagues [6] reported a 71% (n ¼ 88 patients) rate of alive discharge. However, both the CESAR trial and the Danish study had relatively short ECMO support durations (9 days).…”
mentioning
confidence: 96%
“…The survival results of this study were also compared with other published reports and ELSO annual reports to compare short (0-13 days) and prolonged duration ECMO outcomes. 1,3,[21][22][23] Data are reported as mean AE standard deviation (SD) for normally distributed data or median and interquartile range (IQR) for nonnormal data. Continuous variables were compared between 2 groups using the independent Student t test, the Mann-Whitney U test, or 1-way ANOVA, as appropriate.…”
mentioning
confidence: 99%